ACTION DEL AZUL DE METILENO SOBRE LA RESPIRACION INSENSIBLE EN EL CONEJO - PI SUNER, JAIME (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1943)
The placenta of various spp was stained by the Ag impregnation technique of Rio Hortega to reveal the connective fibrils and collagenous and precollagenous structures The histologic study of the placenta of the mouse, rat, and cow is described
BOL INST ESTUD MED BIOL
Keywords: ACTION, AZUL, METILENO, PERSPIRACIÓN, INSENSIBLE, CONEJO; CIENCIAS MEDICAS; FARMACOLOGIA; FARMACOLOGIA EXPERIMENTAL